Comparison of health care professionals' and laypeople's knowledge, attitudes, and practices on the use of antimicrobial and antimicrobial resistance - Tileshkumar B Turankar; Shilpa A Gaidhane; Abhay M Gaidhane; Akshayata G Sorte; Shantanu R Sawale (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The discovery of antimicrobials is a pioneering step in health sciences concerning preventive care and early management for infectious diseases. However, with advancements in health sciences, inappropriate knowledge, practices, and over-the-counter medications were often used by the general population in underdeveloped nations like India without thinking about its consequences which leads to the use of antimicrobials excessively or inadequately, which is also a factor for antimicrobial resistance. This quantitative study determines the awareness of healthcare professionals and laypersons about usage and resistance of antimicrobials.METHODS AND MATERIALS: Research was carried out in rural tertiary teaching hospital of study participants were 106 nurses, 115 interns, 107 junior residents, and 97 laypersons using a "self-administered WHO questionnaire". SPSS version 27.0 software was used to analyze the data. The P value cut-off for significance was established at <.05.RESULTS: Forty seven percent of nurses and 44% of interns consumed antimicrobials in the last month, more than interns and junior residents. Fourteen percent of interns and 13% of laypersons did not get any prescription for lastly taken antimicrobial. The majority of participants obtain prescribed antimicrobials from medical stores and pharmacies. Fifty five percent of laypersons and 59% of nurses stop taking antimicrobials when they feel better. Only 13% of nurses were aware of the proper indications of antimicrobials for the same illness. Only 22% of respondents know the term superbugs, significantly less than the other key terms related to the antimicrobials. Nurses and laypersons had some misconceptions related to the mechanism of development of antimicrobial resistance.CONCLUSIONS: The analysis revealed that a significant lack of knowledge and various misconceptions were primarily seen in the nurses and laypersons. In contrast, medical graduates such as interns and junior residents lacked the right attitude and perspective regarding the use of antimicrobials and their resistance.